Perkaitan antara Pencapaian Akademik dan Ciri Personaliti : Satu Kajian Kes di Kolej MARA - Zol Hamidy, Che An (2003)
The main purpose of the study is to determine the relationship between personality traits and academic achievements/performance. A case study was done at a matriculation college and 214 respondents were selected to be given The Sidek Personality Inventory Test (IPS). Respondents were selected not at random but selection were done according to their academic performance at matriculation examinations. Students with high academic achievement (CGPA>3.5) were grouped together and students with low academic achievement; (CGPA <2.4) were also grouped together. Their personality profiles were analyzed using Sidek Personality Inventory scoring system. It was found that there is a significant difference in the personality profiles of the high achievers compare to low achievers. The basis of comparison was by using the mean score of IPS for each personalily traits and non-parametric test done on the mean score. The study also found significant differences in the personality profiles of the male high achievers and female high achievers namely in the traits of agressiveness and introversion. In general the study supports the finding of many similar studies which found conclusive evidence showing the differences in the personality profiles of high achievers and low achievers.